Hypoglycemic Activities of Aqueous and Methanol Leaf Extract of Hybanthus enneaspermus and Paquetina nigricense on Normal and Alloxan Induced Diabetic Female Sprague Dawley Rats - I.I. Olatunji-Bello, F.O. Awobajo (Journal of Phytology, 2010)
Objective: Glycemic activities of aqueous and methanol leaf extracts of two medicinal plants commonly used by Traditional Birth Attendants in antenatal care in southwest Nigeria were investigated in 105 adult male Sprague Dawley rats. The two plants are Hybanthus Enneaspermus (HE) and Parquetina nigricense (PN). The study was carried out in four phases which are hypoglycemic study and Oral glucose tolerance test. Design: The 85 rats used for the hypoglycemic study was grouped into Control, Aqueous leaf extract of PN (PNaq) treated, Methanol leaf extract of PN (PNmeth) treated, Aqueous leaf extract Ã‚Â of HE (HEaq) treated and Methanol leaf extract of HE (HEmeth) treated group. Each group except the control has 4 sub groups of five rats each. The animals were fasted over night (12hrs), and fasting blood glucose level taken as well as blood glucose level after oral administration of the graded doses of each plant extract every thirty minutes for twelve hours, using a standardized one touch glucose meter. The animals were allowed free assess to water throughout the period of the experiment. Results: The effective hypoglycemic dose (EHD) for HE(aq) and HE(meth) was obtained at 80mg/kg and 180mg/kg body weight respectively. This gave a percentage reduction of whole blood glucose level of 44.15 Ã‚Â± 0.46 at 7hrs and 44.94Ã‚Â±0.32 at 10hrs respectively. On the other hand, the EHD of PN (aq) and PN (meth.) was obtained at 80mg/kg body weight and 160mg/kg body weight respectively. This also gave a percentage whole blood glucose reduction of 46.59Ã‚Â±0.35 at 4hrs and 48.03Ã‚Â±0.44 at 9hrs respectively. A total number of 30 rats were further used to check for the effect of the EHD of the extracts on Oral glucose tolerance test (OGTT). All animals in this test were giving 1.071g/kg body weight of glucose after 12hrs fasting along with the corresponding effective dose of the extracts. HEaq gave a similar hypoglycemic result as Glibenclamide a standard hypoglycemic drug while all others shows different degree of hypoglycemic effects. Conclusion: The potential hypoglycemic activities of the aqueous leaf extracts of PN and HE could be of benefit in its use by the Traditional Birth Attendants in South west Nigeria in correcting Gestational diabetes. But care must be taking in its indiscriminate use to prevent a situation of energy deprivation both for the mother and the developing fetus.